Evaluation of antioxidant and hepatoprotective effects of white cabbage essential oil - Javier Morales-López; Mónica Centeno-Álvarez; Antonio Nieto-Camacho; Mercedes G. López; Elizabeth Pérez-Hernández; Nury Pérez-Hernández; Eduardo Fernández-Martínez (Taylor & Francis Group, 2017)
Context: There have been no reports of the extraction of essential oil (EO) from white cabbage [Brassica oleracea L. var. capitata (L.) Alef. f. alba DC. (Brassicaceae)] (Bocfal) or its chemical composition, antioxidant activity, or hepatoprotective effects. Objective: To extract Bocfal EO, to identify and quantify its chemical components, to assess their antioxidant capacity, and to evaluate the hepatoprotective properties of Bocfal EO. Materials and methods: Bocfal EO was obtained using hydrodistillation (200 mm Hg/58 °C). The chemical composition was analyzed using GC-MS and was quantified using GC-FID. The antioxidant activity of Bocfal EO and its main constituents was evaluated using TBARS in rat brain homogenates. A Bocfal EO hepatoprotective effect (192 mg/kg) on acute carbon tetrachloride (CT)-induced liver damage was determined in rats using biochemical markers and histological analysis. Diallyl disulphide (DADS) (1 mmol/kg) was used as a control for comparison. Results: Bocfal EO contained organic polysulphides (OPSs), such as dimethyl trisulphide (DMTS) 65.43 ± 4.92% and dimethyl disulphide (DMDS) 19.29 ± 2.16% as major constituents. Bocfal EO and DMTS were found to be potent TBARS inhibitors with IC50 values of 0.51 and 3 mg/L, respectively. Bocfal EO demonstrated better hepatoprotective properties than did DADS (p < 0.05), although both slightly affected the hepatic parenchyma per se, as observed using histopathology. Discussion and conclusion: The antioxidant properties of Bocfal EO and DMTS may be the mechanism of hepatoprotective action; the parenchymal disturbances by Bocfal EO or DADS alone may be related to the high doses used.